2016
DOI: 10.1002/jmri.25418
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation of benign prostatic hyperplasia: Correlation with international prostate symptom score

Abstract: 3 J. Magn. Reson. Imaging 2017;45:917-925.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
2
21
1
Order By: Relevance
“…Park et al [1] found that higher PUA ≥ 34°was significantly correlated with IPSS in BPH patients. In contrast to this study, Guneyli et al [2] stated that PUA had no significant correlation with IPSS, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Park et al [1] found that higher PUA ≥ 34°was significantly correlated with IPSS in BPH patients. In contrast to this study, Guneyli et al [2] stated that PUA had no significant correlation with IPSS, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…The relationship between TZV and TPV as regards the IPSS was controversial. Guneyli et al [2] described a significant correlation between TZV and TPV with IPSS. However, Kaplan et al [14] described a stronger correlation between TZV and IPSS and a weak correlation between TPV and IPSS.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations